480-GHz Sensor With Subharmonic Mixer and Integrated Transducer in a 130-nm SiGe BiCMOS Technology - Defu Wang, Mohamed Hussein Eissa, Klaus Schmalz, Thomas Kämpfe, Dietmar Kissinger (IEEE Microwave and Wireless Components Letters, 2020)
A 480-GHz sensor consists of signal stimulus and the transducer element as well as a subharmonic mixer in a 130-nm SiGe BiCMOS technology is reported. It features a mixer-first architecture based on down-conversion subharmonic mixer, an local oscillator (LO) chain at 240-GHz using a frequency doubler with variable-gain characterization, and a 480-GHz RF chain, making the fully integrated 480-GHz receiver possible. In a frequency range of 210–270 GHz at a maximum of 1.5-V supply offset, the LO chain has a 14-dB power-level variation, comprising with a 120-GHz frequency quadrupler, a power amplifier, and a variable frequency doubler. The proposed subharmonic receiver is driven by the RF and LO chain with a multiplier factor of 16 and 8, respectively. In this way, 480-GHz signal is generated, fed through the transducer, and hetero-mixed at subharmonic mixer. The measured output power difference is adjustable over 8 dB. Along with the intermediate frequency (IF) bandwidth of 20 GHz, the wide RF bandwidth makes it suitable for submillimetre-wave receiver-based dielectric spectroscopy applications. The chip occupies an area of 2.2 mm 2 and consumes 290 mW.